KEBIJAKAN PEMERINTAH DAERAH KABUPATEN KAMPAR DALAM PELAYANAN JAMINAN KESEHATAN NASIONAL DI KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR (2012-2015) - Muhammad Arius; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The type of research used is descriptive with the method of skin, with the basis of case study research. Technique of collecting data with observation technique, that is collecting data by literature study, document and result of research and also through institution related to problem which observed and conducted direct observation of object that was researched by using interview technique where researcher held direct question and answer with informant Which is considered to have the quality and ability to address this issue. As for the population in this study is, bureaucratic apparatus Government Kampar regency that has a relationship with the problem of public health services and health care recipients that is the community in the district koto Kampar Hulu, with the technique of sampling is determined by Purposive Sampling, then the results will be processed data and Analyzed qualitatively.                     The result of the research shows that the Local Government Policy in Public Health Service in Kampar Regency is contained in Regent Regulation No. 05 of 2015 on the National Health Insurance System, which aims to provide convenience for the community to procure quality and comprehensive health services to the community. Implementation of the policy according to some managers of the Regional Health Insurance System is good, but in fact there are some obstacles that involve the policy is not running as it should be. Human Resources Factors, Supporting Facilities and Infrastructure for Health Services, disposition / behavior of health service personnel, as well as lack of budget stability in support of the policy are some obstacles that result in the implementation of the policy is not working as it should. Keywords : government policy, National Health Insurance Service